Presence of Otobius megnini (duges, 1883) in cattle in Malatya - Özer, Edip; Aydin, Levent (Scientific and Technical Research Council of Turkey, 1996)
This study reports the results of studies designed to search O. megnini nymphs in cattle. For this purpose, 20 cattle in Kelhalil village in Malatya Do?anşehir county were examined in November 1988. Seven mites were collected during this study and two of these mites were first stage O. megnini nymphs. The rest were second stage well fed O. megnini nymphs. Average lengths and widths of the first stage and the second stage mites were 5.7 × 3.3 and 9.5 × 4.5 mm, respectively. The mites had a spinoid outer surface. After storage in alcohol, first stage mites appeared gray white in color whereas second stage mites were yellow, reddish and brown colored. This report, for the first time, indicates that O. megnini nymphs are present in Turkish cattle.
Malatya'da Si?irlarda Otobius megnini (Duges, 1883)'nin Bulunuşu
Keywords: Cattle; Nymph; Otobius megnini